2010
DOI: 10.1038/nnano.2010.24
|View full text |Cite
|
Sign up to set email alerts
|

Detection of single-molecule H2O2 signalling from epidermal growth factor receptor using fluorescent single-walled carbon nanotubes

Abstract: An emerging concept in cell signalling is the natural role of reactive oxygen species such as hydrogen peroxide (H2O2) as beneficial messengers in redox signalling pathways. The nature of H2O2 signalling is confounded, however, by difficulties in tracking it in living systems, both spatially and temporally, at low concentrations. Here, we develop an array of fluorescent single-walled carbon nanotubes that can selectively record, in real time, the discrete, stochastic quenching events that occur as H2O2 molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
211
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 235 publications
(218 citation statements)
references
References 44 publications
6
211
0
1
Order By: Relevance
“…Our data provide the missing link between agonist-evoked calcium signals and ROS production, which were previously described to be connected in epidermal cell lines (9). EGF-induced H 2 O 2 production by A431 cells was originally described by Bae et al (8) and was subsequently confirmed by several other groups (22), (23). In a recent work, the phagocytic NADPH oxidase, Nox2 was detected in A431 cells, however no attempt was made to establish a correlation between ROS production and Nox2 expression (24).…”
Section: Discussionsupporting
confidence: 69%
“…Our data provide the missing link between agonist-evoked calcium signals and ROS production, which were previously described to be connected in epidermal cell lines (9). EGF-induced H 2 O 2 production by A431 cells was originally described by Bae et al (8) and was subsequently confirmed by several other groups (22), (23). In a recent work, the phagocytic NADPH oxidase, Nox2 was detected in A431 cells, however no attempt was made to establish a correlation between ROS production and Nox2 expression (24).…”
Section: Discussionsupporting
confidence: 69%
“…To confirm that dequenching of Cy3 occurs when the fluorophore destacks from the SWCNT surface, we performed a positive control to confirm simultaneous dequenching and destacking for (GT) 15 − Cy3−SWCNT. To the same surface-immobilized (GT) 15 − SWCNT we introduced 100 nM unlabeled (AC) 6 oligonucleotide, which is complementary to the ends of (GT) 15 −Cy3 DNA. Upon introduction of the (AC) 6 oligonucleotide to the microfluidic channel, we observed the same dequenching of the terminal Cy3 dye from the SWCNT surface [from 10.4 ± 0.8 pre-(AC) 6 to 60.7 ± 1.6 post-(AC) 6 (mean ± SE); Figure 4b], albeit at a lower rate due to the slower hybridization dynamics of (AC) 6 to the terminal end of (GT) 15 −Cy3 DNA.…”
Section: ■ Resultsmentioning
confidence: 99%
“…The main effort in RONS sensing has been devoted to the construction of fluorescence probes because of the high sensitivity and nonionizing nature of fluorescence imaging. [2] Although small-molecule fluorophores, [3] genetically encoded proteins, [4] fluorescent single-walled carbon nanotubes (SWCNs), [5] quantum dots (QDs), [6] and dye-conjugated inorganic nanoparticles [7] have been developed for this purpose, probes applicable for in vivo imaging are still very limited. [2] In addition to near-infrared (NIR) fluorescence, one of the most important prerequisites for in vivo RONS imaging is the resistance of the reporter moiety of the probe to degradation by RONS.…”
Section: Abstract Semiconducting Polymers; Rons; Nanoparticles; Biosementioning
confidence: 99%
“…The limit of detection for those RONS is determined to be ~10 nM in solution, which is comparable to or even lower than previously reported probes. [2][3][4][5][6][7] The combination of the RONS sensitivity of NanoDRONE with its nearly unchanged fluorescence after RONS activation under physiological conditions (Supporting Information, Figure S6) makes it feasible for in vivo RONS imaging.The ability of NanoDRONE to detect RONS was further examined in solution under bioinspired conditions of RONS generation. 3-Morpholinosydnonimine (SIN1), which spontaneously releases NO and O 2 •− to form ONOO − in aqueous solution, was used to mimic the generation of ONOO − by macrophages.…”
mentioning
confidence: 99%
See 1 more Smart Citation